Kingdom of Morocco : Climate Change Strategy Notes - World Bank (Washington, DC, 2014)
This volume contains the individual reports produced under the World Bank program of economic and sector work (P-ESW) on supporting Morocco's climate change strategy. In 2008 the Government of Morocco asked the Bank's analytical and technical assistance on the policy implications of climate change. An initial policy note outlining the main drivers of climate vulnerability, as well as the relationship between climate mitigation and energy security for the country was presented to the Government. The deliverables under the program stem from analytical needs identified from various departments and agencies. Following the conference, a steering committee composed of the department of environment, the ministry for economic and general affairs, and the ministry of economy and finance was set up to oversee the preparation of various analytical outputs supporting the Government's climate policy. It was agreed that the P-ESW will deliver products immediately accessible to the various stakeholders in line with their climate policy objectives. The deliverables will be released as a set of strategy notes, whose content will feed into the development of the Government's sustainable development strategy. The P-ESW program was articulated in three main deliverable blocks: institutional and policy framework; decision support tools; and costing impacts and policies.